Quantifying velocity response to ocean tides and calving near the terminus of Jakobshavn Isbræ, Greenland. Issue 222 (2014) - Podrasky, David; Truffer, Martin; Lüthi, Martin; Fahnestock, Mark
Abstract: Dynamic changes on Greenland outlet glaciers are a primary driver for increases in ice-sheet mass loss and its contribution to sea-level rise. One dramatic example of such change has been observed at Jakobshavn Isbræ, which has thinned, retreated and doubled in speed since the early 2000s. Complementary to large changes on decadal scales, we observe the glacier response on shorter timescales, driven by tidal forcing and calving events. During a 14 day period in August 2009, we documented changes in geometry and speed near the terminus. On this timescale, ice flow responds to forcing at the front from iceberg calving and ocean tides. We observe a step-increase in velocity near the terminus during a large calving event, with transient deceleration in the days following the event. A simple calving-response model explains 94–99% of variations in detrended positions at the four sites considered. During each day, variability due to tidal forcing covers 10–90% of the variability that remains after removing effects accounted for by the calving-response model. The influence of the tidal forcing on flow decays upstream with a characteristic length scale of 2 km, comparable with about two ice thicknesses.